Wojna w dystopii – dystopia jako antywojna (na materiale powieści Kaharłyk Ołeha Szynkarenki) - Ursulenko, Anna (Slavia Occidentalis, 2016)
The dystopian novel Kaharlyk (2014) by Oleh Shynkarenko, the action of which takes place in about 2144, depicts various kinds of wars and forms of armed struggle: the occupation of territories of Ukraine by the Russian army, Russian-Chinese nuclear war, guerrilla warfare, the local conflict for power, and ethnic antagonisms. The description of the post-apocalyptic reality Grey Zone gives the author an opportunity to reflect on the dangers of aggressive ideology: imperialism, religious fundamentalism and radical nationalism. The diagnosis of Ukrainian society presented is also alarming. Hence, the work can be seen as a warning novel. Similar elements can be found in many dystopias written recently in different countries. An analysis of examples from Russian and American cultures shows that criticism of the existing situation is often combined with an admonition of the phenomena that may arise from the dangerous trends of the present, including armed conflicts. Hence visions of future wars, among other things, serve as a tool of discreditation against the ruling political forces and propose an analysis of discourses responsible for driving those wars. Implemented in such way, the ideological function, the metadiscursive perspective and humanistic values of dystopia allow for it, in our opinion, to be included in the arsenal of measures designed to “create conditions that scare of war or limit its scope” (A. Toffler, H. Toffler). The totality of these measures was defined by Alvin and Heidi Toffler as “anti-war”.